Cannabinoid Receptor Type 1 and mu‐Opioid Receptor Polymorphisms Are Associated With Cyclic Vomiting Syndrome. (June 2017) - Wasilewski, Andrzej; Lewandowska, Urszula; Mosinska, Paula; Watala, Cezary; Storr, Martin; Fichna, Jakub; Venkatesan, Thangam
Abstract : Objectives: Cyclic vomiting syndrome (CVS) is a disorder defined by recurrent, unexplained episodes of severe nausea and vomiting. Our aim was to investigate whether CVS and pathophysiological mechanisms underlying this condition are associated with selected variations in genes encoding the components of the endogenous cannabinoid and opioid systems. Methods: This case–control study included 65 patients with CVS‐16 male and 49 female, and 1, 092 healthy controls‐525 male and 567 female from the 1000 Genomes Project. CVS subjects filled out study‐specific questionnaires. Single‐nucleotide polymorphisms (SNPs) in genes encoding cannabinoid receptors ( CNR1 and CNR2 ), fatty acid amide hydrolase ( FAAH ) and mu‐opioid receptor ( OPRM1 ) were analyzed using the TaqMan SNP genotyping assay. Correlations between SNP's and clinical characteristics of CVS were ascertained. Results: Our study disclosed an increased risk of CVS among individuals with AG and GG genotypes of CNR1 rs806380 ( P <0.01), whereas the CC genotype of CNR1 rs806368 and AG and GG genotypes of OPRM1 rs1799971 were associated with a decreased risk of CVS ( P <0.05). In addition, AG and GG genotypes of OPRM1 rs1799971 were correlated with migraine episodes, AG and GG of OPRM1 rs1799971, and CT and CC of CNR1 rs806368 with a family history of migraines (second degree relatives), and CT and CC of CNR1 rs2023239 with a positive response to therapy. Conclusions: Our results show for the first time that the variations in CNR1 and OPRM1 genes are associated with CVS and that different genotypes may contribute to the risk of CVS.